Concepts of the kazakh philosophy in historical development (Journal of Philosophy Culture and Political Science, 2018)
In article the concepts of the Kazakh philosophy important not only in historical aspect, but also in the modern world are considered. Such concepts as ideology of political unity, preserving the earth and culture, humanity become urgent. The ideology of political unity appears as the rod concept, since the Turkic period to modern Kazakhstan, expressed in ideology “Mangilik el”. This concept is submitted as searches of the earth where there is no death (Korkyt-ata) an ideology of “Zheruyiyk”, classification of societies in al-Farabi’s philosophy, Balasagun’s poem “Kutadgubilik” as balance of four moral virtues: Happiness, Justice, Moderation, and Mid. Humanistic searches of the Kazakh philosophy appear as the bases of human life, society. Humanity appears as set of moral requirements in relation to the nature, culture, the person. These specifics are caused by integrity and a dialectic outlook of Kazakhs. The problem of the person is presented to philosophies of Abay most conceptually. In article is considered also historical periods of the Kazakh philosophy, feature of her outlook, starting with religious and mythological, philosophical and art (Korkyt ata, Asan Kaygy), religious and mystical (Yassaui, Bakirgany), socio-political (Balasaguni) of forms to rational and logical attitude (al-Farabi) and philosophical journalism and lyrics (Shokan, Abay, Magzhan). However, despite variety of styles of philosophy, the Kazakh philosophy kept unity of world outlook and valuable installations throughout history. This circumstance appears as a factor of unity and a continuity of the Kazakh life in the history.Key words: Kazakh philosophy, morals, Kazakh Education, al-Farabi’s philosophy, Abay, humanity, political philosophy.